Local perceptions toward social and cultural impacts of tourism in Kampung Benuk, Kuching - Sita, Sharon Esther Anak Donny (2015)
The impacts of tourism have been discussed extensively by researchers attempting to examine the perceptions of the local residents towards the homestay programme. However, past researchers only focused on the perceptions of the homestay operators. The findings of these studies showed that all the perception of the local residents were not included in the studies. Therefore, a study in Kampung Benuk (KB) Homestay, Kuching was conducted to examine the perceptions of the local residents on social and cultural impacts of tourism based on different degrees of contact between the local residents and the tourists, and to analyse local residents’ perceptions that determine their support for additional tourism development or restrictions on tourism development. A qualitative method was employed in this study. A semi-structured interview with twelve local residents who were categorised into ‘high contact’, ‘medium contact’, and ‘low contact’ was conducted in December 2013. A snowball sampling was undertaken and the data were analysed manually. The study revealed that the ‘high contact’ respondents perceived the homestay programme positively and supported additional tourism development. The ‘medium contact’ respondents perceived that tourism had more costs than benefits. However, the respondents were positive towards additional tourism development. The ‘low contact’ respondents seemed to support both the additional tourism development and the restrictions, although they did not participate in the homestay programme. The findings of this study provide strategies for the government and other tourism agencies to overcome issues faced by the local residents and increase the benefits of the homestay programme